Ferroptosis Contributes to Neuronal Death and Functional Outcome After Traumatic Brain Injury - Kenny, Elizabeth M; Fidan, Emin; Yang, Qin; Anthonymuthu, Tamil S; New, Lee Ann; Meyer, Elizabeth A; Wang, Hong; Kochanek, Patrick M; Dixon, C Edward; Kagan, Valerian E; Bayir, Hülya (Critical care medicine, 2019)
Traumatic brain injury triggers multiple cell death pathways, possibly including ferroptosis-a recently described cell death pathway that results from accumulation of 15-lipoxygenase-mediated lipid oxidation products, specifically oxidized phosphatidylethanolamine containing arachidonic or adrenic acid. This study aimed to investigate whether ferroptosis contributed to the pathogenesis of in vitro and in vivo traumatic brain injury, and whether inhibition of 15-lipoxygenase provided neuroprotection. Cell culture study and randomized controlled animal study. University research laboratory. HT22 neuronal cell line and adult male C57BL/6 mice. HT22 cells were subjected to pharmacologic induction of ferroptosis or mechanical stretch injury with and without administration of inhibitors of ferroptosis. Mice were subjected to sham or controlled cortical impact injury. Injured mice were randomized to receive vehicle or baicalein (12/15-lipoxygenase inhibitor) at 10-15 minutes postinjury. Pharmacologic inducers of ferroptosis and mechanical stretch injury resulted in cell death that was rescued by prototypical antiferroptotic agents including baicalein. Liquid chromatography tandem-mass spectrometry revealed the abundance of arachidonic/adrenic-phosphatidylethanolamine compared with other arachidonic/adrenic acid-containing phospholipids in the brain. Controlled cortical impact resulted in accumulation of oxidized phosphatidylethanolamine, increased expression of 15-lipoxygenase and acyl-CoA synthetase long-chain family member 4 (enzyme that generates substrate for the esterification of arachidonic/adrenic acid into phosphatidylethanolamine), and depletion of glutathione in the ipsilateral cortex. Postinjury administration of baicalein attenuated oxidation of arachidonic/adrenic acid-containing-phosphatidylethanolamine, decreased the number of terminal deoxynucleotidyl transferase dUTP nick-end labeling positive cells in the hippocampus, and improved spatial memory acquisition versus vehicle. Biomarkers of ferroptotic death were increased after traumatic brain injury. Baicalein decreased ferroptotic phosphatidylethanolamine oxidation and improved outcome after controlled cortical impact, suggesting that 15-lipoxygenase pathway might be a valuable therapeutic target after traumatic brain injury.